(untitled) (TAMADDUN NURI JURNALI, 2025)
Reading English literature offers significant psychological benefits that contribute to personal growth and emotional well-being. Through engagement with diverse characters, complex narratives, and rich cultural contexts, readers develop empathy, critical thinking, and emotional resilience. English literary works allow individuals to explore a wide range of human experiences, providing a safe space for self-reflection and emotional processing. Furthermore, literature serves as a tool for stress reduction and cognitive stimulation, promoting mental flexibility and creativity.